The acceptability of HPV vaginal self-sampling for cervical cancer screening in Latin America: A systematic review - Luisa Narvaez; Manuela Viviano; Cheryl Dickson; Emilien Jeannot (Elsevier, 2023)
Objective: This review summarizes women's acceptability of vaginal self-sampling for cervical cancer screening in Latin America. Study design: Systematic review Method: A systematic literature search was performed in PubMed, Web of Science, and Embase regarding the acceptance of HPV vaginal self-sampling by women over 18 years old. Articles were selected for research that was conducted in Latin America and published between January 1st, 1993, and December 31st, 2022. Results: Fifteen publications were included. Eight publications reported an acceptance of HPV self-sampling as high as 80%, six papers found an acceptance rate between 50 and 80% and only one found an acceptance rate of less than 50%. Based on non-standardized questionnaires, women considered self-sampling more comfortable, easier, and less painful than conventional cytology. The procedure was associated with less embarrassment and a greater sense of privacy. Conclusion: HPV vaginal-self sampling appears to be an acceptable screening method amongst eligible Latin American women.